FATALI KHAN’S FOREIGN POLICY ACTIVITY - Magomedov, N A (History, Archeology and Ethnography of the Caucasus, 2017)
The article is devoted to the study of main directions of foreign policy of Fatali Khan, the khan of Derbent and Quba, in the 80s of the 18thcentury. The study has shown that Fatali Khan conducted rather an active foreign policy. He had the closest contacts with the Russian Empire. Fatali Khan many times addressed a request to the Imperial Court to get Russian citizenship, sent his ambassadors to discuss and solve various problems including normalization of trading relations with Russia. In his letters, the Khan asked for trade privileges for Derbent merchants, on his part he gave Russian merchants the right for duty-free trade in the Derbent-Quba khanate and other territories under his influence. The author of the article analyzes FataliKhan’s policy on expanding the territory of his possession on account of other Dagestan and Azerbaijan lands, and his allied relations with ShamkhalTarkovsky.The Khan’s relationswith other Dagestan rulers were not easy as they stood against his policy of expanding the borders of the Derbent-Quba khanate. Another direction of the foreign policy of the Khan of Derbent and Qubawas his relationship with the Georgian prince Alexander, whose actions were directed not only against the Kingdom of Kakheti and Kartli, but also against the Russian authorities. Therefore, Fatali Khan refused to support the Georgian prince.
Keywords: North-Eastern Caucasus; Derbent Khanate; Fatali Khan; foreign policy; relations with Russia; regional policy